Parallel multistep block method for solving large systems of ODEs - Abdul Majid, Zanariah (Universiti Putra Malaysia, 2016)
The parallel solution of ODE has received interest from many researchers due to the possibility of using parallel computing platforms. In this research, we will introduce the block method that will compute the numerical solution of ordinary differential equations (ODEs) of the form.